PERANAN PENDIDIKAN KEWARGANEGARAAN DALAM MEMBINA SIKAP TOLERANSI ANTAR SISWA - Sofian Abdulatif; Dinie Anggraeni Dewi (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
THE ROLE OF CITIZENSHIP EDUCATION IN FOSTERING TOLERANCE AMONG STUDENTSThis study aims to determine the role of civic education in fostering tolerance among students. the role of civic education in fostering tolerance among students, these students interact with each other, respect each other, respect each other, help each other. There has never been hostility and there has never been conflict between them and they have never differentiated between one religion and another. the tolerance they have had is well done. So it seems clear that the role of civic education is already running as it should be in accordance with what is taught in Citizenship Education.